Effects of Transmission Ratio on the Nonlinear Vibration Characteristics of a Gear-Driven High-Speed Centrifugal Pump. (8th January 2021) - Zhou, Anmin; Zhai, Lulu; Zhu, Zuchao; Guo, Jia; Zhang, Xinglin; Cui, Baoling
Abstract : The gear transmission system is widely used in high-speed centrifugal pump to improve the operating speed and hydraulic performances of the whole pump. Vibration characteristics and the stability of these high-speed rotor systems with gear transmission have great impacts on the stability of the whole fluid transmission system of the plant. Based on the lumped-mass method and the principle of displacement equilibrium of the rotor system, a coupled lateral-torsional dynamic model describing the gear-rotor-seal-bearing (GRSB) system of high-speed centrifugal pumps which has considered the nonlinear factors within the gear pair, nonlinear forces of bearings, and those of the seals is proposed. Then, the stability and nonlinear vibration responses of a model GRSB system under different gear transmission ratios ( i ) have been studied. The following conclusions are drawn from the results: (1) The components with frequencies like f p, f g, f m, and 2 f m have great impacts on the vibration responses of the gear pair, especially the f m component; moreover, the amplitude of f m first increases and then decreases with the ratio increase and reaches the maximum value under the ratio of 3. (2) A jump motion state will occur when the ratio i is 1.25 and the stability of the system is obviously worse than the bifurcation state. Quite different from those under the other states, under this jump motion state, the 0.2f g component and 0.5 f p component will appear in the vibration responses of both gears and become the most contributed two factors to the responses of the driven gear. (3) In the design process, the transmission ratio of a high-speed centrifugal pump with a simplified GRSB system should be specially designed to avoid the jump-point state and the maximum-amplitude-of- f m state to ensure the stability of the system as well as reduce the mechanical impacts and noises.